Red storm rising - Clancy, Tom, 1947-2013 (G.P. Putnam's Sons, 1986)
When Moslem fundamentalists destroy a key Soviet oil complex, the Russians initiate a plan of diplomatic trickery for their seizure of Persian Gulf oil.